2012
DOI: 10.1007/s10815-011-9694-6
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the vaginal microbiome during infertility therapy with in vitro fertilization-embryo transfer

Abstract: This metagenomics approach has enabled discovery of novel, previously unidentified bacterial species in the human vagina in different hormonal milieu and supports a shift in the vaginal microbiome during IVF-ET therapy using standard protocols. Furthermore, the data suggest that the vaginal microbiome on the day of embryo transfer affects pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 28 publications
6
120
0
7
Order By: Relevance
“…These findings are consistent with a recently published cross-sectional study of the microbiota of the cervix, posterior fornix and vaginal canal in a limited number (n = 5) of samples collected postpartum42. This dynamism provides evidence that oestrogen is likely an important factor in shaping the composition of the vaginal microbiome, particularly during pregnancy4344. During pregnancy, placental production of oestrogen causes circulating concentrations to rise dramatically4546.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with a recently published cross-sectional study of the microbiota of the cervix, posterior fornix and vaginal canal in a limited number (n = 5) of samples collected postpartum42. This dynamism provides evidence that oestrogen is likely an important factor in shaping the composition of the vaginal microbiome, particularly during pregnancy4344. During pregnancy, placental production of oestrogen causes circulating concentrations to rise dramatically4546.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, a lactobacilli-dominated VMB was associated with a reduced risk of pre-term birth, a higher likelihood of IVF resulting in a live birth, and a reduced risk of vaginal dryness in postmenopausal women in one study each [49], [69], [78].…”
Section: Resultsmentioning
confidence: 84%
“…This community level change may be indicative of severe, active endometriosis and provide further explanation for decreased rates of pregnancy in these women. Indeed, it has been shown that within the vagina, this shift in microorganisms has been linked to decreases in pregnancy as a result of IVF [33], thus a more thorough, detailed characterization of these communities through time is warranted. Examining the cervical bacterial community of the stage III patient upon follow up visits, we showed that the bacterial community was similar to the DOS two weeks post-surgery, but at the four month post-surgery visit, the cervical bacterial community was 97% Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%